Interaction patterns, knowledge sharing, views and readiness in using Wiki and Skype in collaborative writing among ESL undergraduates in Malaysia - Hiew, Yolanda Lee Lee (2016)
This study investigated the use of computer-mediated communication (CMC) tools, Wiki and Skype, for interaction and collaborative writing among ESL undergraduates in a Malaysian context. A substantial number of studies have emphasised the factors that support wikis as interaction tools in language learning, while some have overtly focused on the use of wikis for group assignments. However, the use of Skype in tertiary setting appears less explored in the literature. Thus, the study investigated how these asynchronous (Wiki) and synchronous (Skype) systems facilitate collaborative writing among ESL undergraduates. The theory of constructivism, social presence theory, and writing theories were employed in this study. In order to contribute to knowledge and understanding about students collaborative activities in a constructivist learning environment, Wang’s Generic Model that covers the framework of pedagogy, social interaction and technology aspects was used. The objectives of the study were to examine the process using Wiki and Skype for collaborative writing and to evaluate the products as a result of using the CMC tools. The research design of this study is primarily qualitative. The quantitative responses served as a supplement for enriching the qualitative part of the study; thus, a mixedmethod research design is applied. This study examined the efficiency of Wiki and Skype for two different collaborative writing tasks. Twenty-five ESL undergraduates pursuing a degree in English Language at a public university in Malaysia participated in the study. The students formed a group of four to five members to complete two collaborative writing tasks using Wiki and Skype for discussion. The written documents were evaluated using the ESL Composition Profile. Knowledge sharing, usefulness and satisfaction questionnaires were administered following the completion of tasks, and a focus-group interview was conducted at the end of the semester with the same participants. Text-conversations from Wiki and Skype were observed for interaction patterns using the coding scheme for online interactions. Content analysis and descriptive statistics were used to analyse the data. The key findings of the study show the differences and similarities between Wiki and Skype in the patterns of interaction, where students informed and gave suggestions. The students had points that are more argumentative in the Wiki discussion forum. Students were satisfied with the group tasks using Wiki and Skype, where Wiki developed writing skills and Skype fostered social interaction. Social presence and team leadership contributed significantly to knowledge sharing in students’ collaboration on Wiki and Skype. The study also shows that language proficiency and technology skills determined student readiness to participate in online collaboration on Wiki and Skype. The written products confirm that students had fulfilled the tasks requirement and they had efficiently completed their collaborative writing through both Wiki and Skype. This study suggests that the use of Wiki should be supplemented by Skype to wholly enhance interaction in the collaborative writing process among ESL undergraduates in a Malaysian context.